PROFESSIONAL DEVELOPMENT OF TEACHERS IN FORMAL AND NON-FORMAL EDUCATION: UKRAINIAN AND FOREIGN CONTEXTS (Comparative Professional Pedagogy, 2021)
The article summarizes Ukrainian and foreign experience in delivering teacher professional development in formal and non-formal education. It shows that Ukraine has taken certain effective measures to improve the system of continuing teacher education (legally regulating professional development in both formal and non-formal education; expanding opportunities for continuing professional development in distance learning; providing material encouragement to teachers based on the results of certification, internships, advanced training, project activities; focusing on the effective development of teacher professional competencies (digital, ICT, innovation); elaborating teacher professional standards). A detailed analysis of the relevant foreign experience has allowed the authors to select valuable educational practices and determine the prospects for improving the system of teacher professional development. These are the following: introducing a gradual trajectory of teacher professional development which contributes to an increase in wages and promotes various social benefits; providing state grants; considering the regional context (including the needs of individual schools); creating appropriate research sites at schools; motivating novice teachers to participate in project activities; organizing effective training of mentors who provide support to students during teacher placement, as well as novice teachers at universities and practical training facilities; developing diversified (in terms of duration and forms) programmes on professional development; providing financial incentives under the results of advanced training, internships; organizing compulsory certification to confirm the teacher’s license; promoting partnership between teacher associations and different organizations, such as the Regional Commonwealth of Schools and Universities and committees for teacher professional development in the regions; enhancing non-formal learning in distance and full-time formats; creating virtual platforms, centres of methodical support in individual fields (language, mathematics, natural sciences) in cooperation with research institutions and universities.
Keywords: continuing teacher education; teacher professional development; formal education; non-formal education; foreign experience; Ukraine